التعريب وأثره في تعليم اللغة العربية لغير الناطقين بها - muhammad zaenuri (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
AbstractThis paper aims to explain ta’rib which is a term from Arabic linguistics. In addition, this paper will also explain how the implications of learning about learning Arabic for non-Arabic learners. Ta'rib is the absorption of new words and terms from non-Arabic languages to Arabic by changing their pronunciation to follow patterns and rules in Arabic. Ta'rib can be done in two ways, first forming a new term to replace foreign terms, the two using foreign languages with Arabic patterns that are in accordance with the stipulated conditions. The implication ta’rib of learning Arabic for learners from outside the Arab world includes 1) giving mufradatfusha before the mufradat ‘amiyyah; 2) emphasize students to use Arabic fusha; 3) emphasize students to look for a translation in the dictionary before absorbing it directly; 4) introducing examples of foreign vocabulary that do not have equivalents in Arabic; 5) explain the provisions that apply to the owner ta’rib before Arabic language learning takes place; 6) emphasizes on students to pay attention to the rules of writing Latin letters that do not have equivalents in Arabic.